2011
DOI: 10.1007/s10826-011-9535-3
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Implementing Wraparound: Results from the State Wraparound Survey

Abstract: The wraparound process has been promoted in the children's services field as a mechanism to achieve collaborative service planning and delivery for families of young people with complex emotional and behavioral needs that span multiple agencies. We compared results of two surveys of state children's mental health directors, completed in 1998 and 2008, to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
(8 reference statements)
0
26
0
Order By: Relevance
“…Though a recent narrative review identified 36 wraparound outcome studies (Suter and Bruns 2008), the majority did not directly compare outcomes between youth receiving wraparound to controls. Although each of the included studies is a unique implementation of wraparound, they represent less than 1% of the estimated 1,000 wraparound programs in the United States (Bruns et al 2008a). Notably, many of the most highly respected and discussed wraparound initiatives are not represented in the current review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though a recent narrative review identified 36 wraparound outcome studies (Suter and Bruns 2008), the majority did not directly compare outcomes between youth receiving wraparound to controls. Although each of the included studies is a unique implementation of wraparound, they represent less than 1% of the estimated 1,000 wraparound programs in the United States (Bruns et al 2008a). Notably, many of the most highly respected and discussed wraparound initiatives are not represented in the current review.…”
Section: Discussionmentioning
confidence: 99%
“…Given the definition of wraparound and its principles, children's mental health directors in 88% of US states and territories reported having at least one wraparound initiative in their state. Results from this study yielded an estimate of over 100,000 youth participating in nearly 1,000 programs (Bruns et al 2008a). Wraparound programs have also been developed in Canada, New Zealand, Norway, and other countries (VanDenBerg 2008).…”
Section: Family Voice and Choicementioning
confidence: 98%
See 1 more Smart Citation
“…The adoption of a 'key worker' model of service delivery, where one person acts as a single point of contact to help a family navigate supports and services across sectors, could dramatically decrease burden on families (Drennan, Wagner & Rosenbaum, 2005). Similarly, implementation of the wraparound process, a system-level intervention to integrate care across sectors, might improve the experiences of families (Bruns et al, 2011). Furthermore, multi-agency and multi-sectoral steering committees for service and policy development that include parents are imperative to decreasing systemic barriers to care.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…While a significant literature has identified issues in the implementation of SOCs (e.g., Center for Mental Health Services 2003; Cook and Kilmer 2004;Holden et al 2003;Kilmer et al 2010b;Kutash et al 2011;Lunn et al 2011;Pandiani et al 1996) and wraparound (e.g., Bertram et al 2011;Bruns et al 2011;Cook et al 2007;Epstein et al 2003;Palamaro Munsell et al 2011;Walker et al 2003;Walker and Schutte 2005), including a Special Issue (Bruns and Walker 2011a) focusing on wraparound services and wraparound implementation, there is scant knowledge regarding the particular elements of wraparound, or the specific characteristics of SOCs, that contribute to more positive outcomes for children and their families.…”
mentioning
confidence: 99%